Acute kidney injury requiring dialysis in obstetric patients: management and clinical outcome in case series of 30 patients in a tertiary care centre - Patel, Molina U.; Jadeja, Yuvraj; Patel, Niket; Patel, Nayana; Vaishnav, Smruti; Bhadarka, Harsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Acute Kidney Injury is a common medical problem affecting approximately 5% of all hospitalized and 30% of critically ill patients. The incidence in obstetric patients ranges from 1 in 2000 to 1 in 25000 pregnancies. In India till date, the impact of AKI on fetomaternal outcome and pertaining therapeutic interventions is only sparsely studied. Methods: It is a retrospective cross-sectional study. All obstetric patients with AKI on dialysis, admitted to Shree Krishna Hospital, a tertiary care hospital in Karamsad village in Gujarat from January 2013 to August 2015. Multivariate statistical analysis of clinical and laboratory parameters was performed using SPSS program to obtain the results. Results: The incidence of dialysis was 1.6%. HELLP syndrome and pre-eclampsia (80%) was found to be the most common etiology of AKI followed by Congestive cardiac failure (34.5%), hemorrhage and sepsis in 30% resp. All patients were admitted to ICU care. No significant difference was found between SAP II and SOFA monitoring system. Mechanical ventilation was done to support 53.3% and inotropic support was needed by 56.7% patients. According to the RIFLE criteria, majority of the patients fall under risk category followed by injury. 18% of the patients developed End Stage Renal Disease. Conclusions: In view of the multifaceted etiologies and complexity of management of AKI, a multi-disciplinary approach involving nephrologist, intensivists, obstetricians and neonatologists is extremely important.